Combination of Bayesian Network and Overlay Model in User Modeling - Nguyen, Loc; Do, Phung (International Journal of Emerging Technologies in Learning (iJET), 2009)
The core of adaptive system is user model containing personal information such as knowledge, learning styles, goalsâ?¦ which is requisite for learning personalized process. There are many modeling approaches, for example: stereotype, overlay, plan recognitionâ?¦ but they donâ??t bring out the solid method for reasoning from user model. This paper introduces the statistical method that combines Bayesian network and overlay modeling so that it is able to infer userâ??s knowledge from evidences collected during userâ??s learning process.